Predictors and Long-term Outcome of Sexual Function After Surgical Treatment for Single-level Lumbar Disk Herniation Among Patients in a German Spine Center. Issue 8 (October 2018) - Elsharkawy, Alaa E.; Lange, Bettina; Caldas, Fernando; Alabbasi, Abdel H.; Klassen, Peter D.
Abstract : Study Design: This is a retrospective, self-controlled cohort study, at a single center. Objective: The aim of this study was to evaluate the long-term outcome of sexual function after surgical treatment of single-level lumbar disk herniation (LDH). Summary of Background Data: The impact of surgical treatment on sexual activity is still unknown and not well researched. Materials and Methods: In total, 114 patients who underwent disk surgery for LDH between 2009 and 2015 were included in the study (mean age, 46.9 y). Two separate questionnaires evaluating general health and all aspects of sexual function were administered to all patients. Results: Satisfaction with the overall outcome of surgery was reported by 84.2% of patients. In total, 82 patients (71.9%) rated their current sexual life as normal with no additional pain, 22 (19.3%) reported a normal sex life with some additional pain, and 2 reported that (2.6%) pain prevents them from having any sex life at all. Compared with their state before LDH and spine surgery, 79 patients (69.3%) rated their sexual function as quantitatively and qualitatively the same as before surgery, 19 patients (16.7%) as better, and 16 patients (14.0%) as worse. The ability to experience orgasm, complete intercourse, experience sexual desire, and experience sexual arousal was reported to be the same as before surgery by 87 (76.3%), 75 (65.8%), 79 (69.3%), and 85 (74.6%) patients, respectively. After surgery, 16 patients (14%) explored new sexual positions. Sexual function receives insufficient attention from physicians. Women reported more general and sexual problems such as decreased sexual desire and interest, taking medication, and seeking regular medical attention. Predictors of the outcome were leg pain, the intensity of back and leg pain, and the professional status of the patient. Conclusions: Lumbar disk surgery has a positive effect on sexual function. The majority of patients returned to their normal sexual activities in long-term follow-up.